(untitled) (Research, Society and Development, 2025)
Acute appendicitis is the leading cause of inflammatory acute abdomen, with high prevalence among children and young adults, particularly in males. Its variable clinical presentation and sometimes asymptomatic nature pose a diagnostic challenge, potentially leading to severe complications, especially in cases of delayed diagnosis. This study aimed to analyze cases of acute appendicitis treated at the Hospital Geral de Nova Iguaçu (HGNI) between July 2023 and June 2024, correlating the degree of appendicular inflammation with postoperative complications and length of hospitalization. Medical records of 437 patients treated at the hospital during the specified period were analyzed, observing criteria related to the patient, disease progression, intraoperative findings, and postoperative outcomes. The study revealed a direct correlation between the disease’s progression and the occurrence of complications, length of hospital stay, and the need for reoperation, all of which significantly influence patient prognosis and hospital costs. In this regard, the importance of early diagnosis and timely intervention for these patients is evident, enabling a better clinical outcome.